2008
DOI: 10.1108/02632770810864998
|View full text |Cite
|
Sign up to set email alerts
|

The impact of facilities management on patient outcomes

Abstract: Purpose of this paperThe aim of the study was to investigate the extent to which practicing NHS facilities managers thought that the contribution of FM could be measured in terms of health outcomes. Design/methodology/approachA questionnaire was distributed to NHS facilities or estate managers from the majority of NHS trusts in England and Wales. FindingsIn general, there is little or no evidence from pre-existing research to prove the contribution of FM in terms of health outcomes. However in spite of this 59… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 3 publications
0
31
0
Order By: Relevance
“…The NHS and the British Medical Association's (BMA) surveys revealed that two of the patients' top ten priorities were FM-issues, namely cleanliness, and hospital food (Miller and May, 2004;May and Pinder, 2008). The NHS has recognised the food's importance, and has launched several initiatives for improvements of the hospitals' food and catering services (May and Pinder, 2008).…”
Section: Fm At Hospitalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The NHS and the British Medical Association's (BMA) surveys revealed that two of the patients' top ten priorities were FM-issues, namely cleanliness, and hospital food (Miller and May, 2004;May and Pinder, 2008). The NHS has recognised the food's importance, and has launched several initiatives for improvements of the hospitals' food and catering services (May and Pinder, 2008).…”
Section: Fm At Hospitalsmentioning
confidence: 99%
“…The NHS has recognised the food's importance, and has launched several initiatives for improvements of the hospitals' food and catering services (May and Pinder, 2008). In 2014, the UK's Department of Health's Hospital Food Standards Panel issued a comprehensive national recommendation for food and drink in the NHS hospitals (Department of Health, 2014).…”
Section: Fm At Hospitalsmentioning
confidence: 99%
“…Secondly, as for space management and FM the infrastructure becomes more important. FM is the object of research in the high educational sector, however, it is the most frequently analyzed from the perspective of managing ISSN 2327-5510 2016 educational space (May and Pinder, 2008;Ogbeifun, 2011;UK Higher ...., 2006;Christensen, Eyring, 2011;Fishman, 2014). The paper's interest is focused on research space, separated from educational one.…”
Section: Educational System In Poland -Transition Context and Exemplimentioning
confidence: 99%
“…The evidence linking high quality space to outcomes, while still less than it might be is growing for schools, (CABE, 2006), offices Price, 2007), universities (Price et al 2003) and hospital environments (e.g. Hutton and Richardson, 1995;Miller and May, 2006;May and Pinder, 2008 ). Such spaces, if they are to be kept in good condition do tend to cost more (per unit area at least); an assertion that should not under value the fact that some facilities management regimes, given the same level of funding, manage to produce different levels of quality (Price and Akhlaghi, 1999;Macdonald 2007;Macdonald et al, in prep ).…”
Section: Figure 1 About Herementioning
confidence: 99%